Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.18632/oncotarget.14378
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 inhibition in multiple myeloma downregulates myeloma associated oncogenes and upregulates microRNAs with potential tumor suppressor functions

Abstract: Multiple Myeloma (MM) is a plasma cell tumor localized to the bone marrow (BM). Despite the fact that current treatment strategies have improved patients' median survival time, MM remains incurable. Epigenetic aberrations are emerging as important players in tumorigenesis making them attractive targets for therapy in cancer including MM. Recently, we suggested the polycomb repressive complex 2 (PRC2) as a common denominator of gene silencing in MM and presented the PRC2 enzymatic subunit enhancer of zeste homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 66 publications
2
62
1
Order By: Relevance
“…By contrast, activated B-cell lymphoma cells are not sensitive to EZH2i, and display modest transcriptional changes upon treatment (McCabe et al, 2012b, Beguelin et al, 2013). EZH2i have been recently described to decrease the expression of oncogenes and promote the expression of miRNAs with tumor suppressor functions in MM cells (Alzrigat et al, 2017). In our study, EZH2i activated a large number of genes in both UTX -mutant and wild-type MM cells, but a substantial fraction of these genes were different, with enrichment of genes involved in cell death and regulation of proliferation found exclusively in UTX -mutant cells.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, activated B-cell lymphoma cells are not sensitive to EZH2i, and display modest transcriptional changes upon treatment (McCabe et al, 2012b, Beguelin et al, 2013). EZH2i have been recently described to decrease the expression of oncogenes and promote the expression of miRNAs with tumor suppressor functions in MM cells (Alzrigat et al, 2017). In our study, EZH2i activated a large number of genes in both UTX -mutant and wild-type MM cells, but a substantial fraction of these genes were different, with enrichment of genes involved in cell death and regulation of proliferation found exclusively in UTX -mutant cells.…”
Section: Discussionmentioning
confidence: 99%
“…As well, because t(4;14) MM is accompanied with a global reduction of the mark added by EZH2, H3K27me (49, 50), EZH2 inhibitors (EZH2i) have been effective at targeting MM cells with elevated levels of NSD2 (51, 6164). Similarly, KDM6A loss in MM led to repression of a specific gene set that can be re-expressed by EZH2 inhibition, leading to cell death (65).…”
Section: Histone Methylation Mediated By Set Domain Methyltransferasesmentioning
confidence: 99%
“…Similarly, KDM6A loss in MM led to repression of a specific gene set that can be re-expressed by EZH2 inhibition, leading to cell death (65). EZH2 inhibitor sensitivity in MM has been attributed to downregulation of MM oncogenes such as c-MYC, XBP-1, IRF-4, PRDM1 (64), and upregulation of epithelial tumor suppressor genes like CDH1 (63). …”
Section: Histone Methylation Mediated By Set Domain Methyltransferasesmentioning
confidence: 99%
“…EZH2 has also been shown to interact with transcription factors which are targets of tumor suppressor miRNAs, such as MYC in lymphomas [61] and in MM [29]. Alzrigat et al demonstrated that pharmacologic inhibition of EZH2 in MM cell lines and primary cells suppressed transcription factors with oncogenic activity in MM including IRF-4, XBP-1, PRDM1/BLIMP-1, and c-MYC.…”
Section: Introductionmentioning
confidence: 99%